Persistent COUP-TFII expression underlies the myopathy and impaired muscle regeneration observed in resistance to thyroid hormone-alpha - Aguiari, Paola (Sci Rep, 2021)
Thyroid hormone signaling plays an essential role in muscle development and function, in the maintenance of muscle mass, and in regeneration after injury, via activation of thyroid nuclear receptor alpha (THRA). A mouse model of resistance to thyroid hormone carrying a frame-shift mutation in the THRA gene (THRA-PV) is associated with accelerated skeletal muscle loss with aging and impaired regeneration after injury. The expression of nuclear orphan receptor chicken ovalbumin upstream promoter-factor II (COUP-TFII, or Nr2f2) persists during myogenic differentiation in THRA-PV myoblasts and skeletal muscle of aged THRA-PV mice and it is known to negatively regulate myogenesis. Here, we report that in murine myoblasts COUP-TFII interacts with THRA and modulates THRA binding to thyroid response elements (TREs). Silencing of COUP-TFII expression restores in vitro myogenic potential of THRA-PV myoblasts and shifts the mRNA expression profile closer to WT myoblasts. Moreover, COUP-TFII silencing reverses the transcriptomic profile of THRA-PV myoblasts and results in reactivation of pathways involved in muscle function and extracellular matrix remodeling/deposition. These findings indicate that the persistent COUP-TFII expression in THRA-PV mice is responsible for the abnormal muscle phenotype. In conclusion, COUP-TFII and THRA cooperate during post-natal myogenesis, and COUP-TFII is critical for the accelerated skeletal muscle loss with aging and impaired muscle regeneration after injury in THRA-PV mice.